Construction of a force method for estimating the longitudinal stability of the process of thin sheet rolling - Romaniuk, Roman; Levchuk, Kateryna; Hasylo, Yurii; Chasov, Dmitry; Kriukovska, Olha (Eastern-European Journal of Enterprise Technologies, 2019)
We have analyzed theoretical features of rolls gripping capacity at simple rolling process under a steady mode. It is shown that depending on the conditions for deformation the ratio of the maximum gripping angle to a friction coefficient can be equal to, be less or more than 2. An experimental study has been performed involving the rolling of lead stepped samples measuring the forward creep at each step. Results of the experiment demonstrate that in the extreme case of deformation the forward creep is greater than zero, that is, there is a sufficient reserve of frictional forces so that reduction can be further increased, however, it is impossible. We have analyzed the balance of all horizontal forces at deformation site. It is shown that at each cross section the stretching horizontal contact forces are used not only to overcome the ejecting ones, but also to compensate for the longitudinal internal forces that occur as a result of plastic deformation of a metal. A force method for estimating the longitudinal stability of the sheet rolling process has been developed. An indicator of stability is a criterion that is determined from the diagrams of distribution of a normal contact stress and the stress of friction. It is shown that at a positive value of the criterion the rolling process proceeds under a steady mode; at a negative value, the stable process is impossible; and in the case it equals zero, the limit deformation occurs. A theoretical study has been conducted into determining the maximum gripping angle under different conditions of sheet rolling. It is shown that the ratio of the maximum gripping angle to a friction coefficient almost does not depend on a strip thickness, the diameter of rolls, as well as friction coefficient, and equals 1.43‒1.44. A decrease in the gripping capacity of rolls is explained by the effect, at a deformation site, not only of contact forces, but the internal forces as well.